2010
DOI: 10.26719/2010.16.5.491
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HIV voluntary counselling and testing services in Egypt. Part 2: service providers' satisfaction

Abstract: Voluntary counselling and testing (VCT) services are major components of HIV prevention and treatment efforts. A study in Egypt aimed to determine the satisfaction of service providers at VCTs to identify strengths and weaknesses in the service. Direct interviews with all 50 VCT team members and focus group discussions with 16 counsellors showed that the majority believed that they had received enough training (90%), but still 66% wanted further training. Only 50% reported receiving sufficient incentives. Prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(22 reference statements)
0
4
1
1
Order By: Relevance
“…The factors identified by the counselors could throw light on the issues that may help in better service delivery at ICTCs. In our study, most of the counselors were females; whereas in the Egyptian 6 and South African studies, 7 male counselors outnumbered the females. The nurse counselors and social workers in cases of South African study 7 had an experience of 8 years that was almost similar to the experience of senior counselors in our study.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The factors identified by the counselors could throw light on the issues that may help in better service delivery at ICTCs. In our study, most of the counselors were females; whereas in the Egyptian 6 and South African studies, 7 male counselors outnumbered the females. The nurse counselors and social workers in cases of South African study 7 had an experience of 8 years that was almost similar to the experience of senior counselors in our study.…”
Section: Discussioncontrasting
confidence: 69%
“…5 Another study conducted by Kabbash et al in Egypt identified a lack of administrative support, unclear working rules and regulations, lack of proper community awareness, the need for further training, the need for a fixed job description, and improved working environment to ensure privacy and confidentiality. 6 Ginwalla et al conducted a study among nurse counselors and community volunteers and emphasized the need for training counselors. 7 The objective of our study was to assess the perceptions of counselors with respect to training received, problems faced in providing services, and job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, it has shifted from prevention actions with material and human resources to a more basic care based model focused on providing diagnoses. Grangeiro et al [ 19 ] came to a similar conclusion in their diagnostic study conducted in the first decade of 2000 and more recent studies have also noted institutional constraints on STD/AIDS counselors’ abilities to provide more personalized and far-reaching support [ 10 12 , 34 ].…”
Section: Discussionmentioning
confidence: 79%
“…Such research highlights the difficulties professionals face, such as overworking or frustration, as a result of a lack of resources (material and human), physical space and long hours. In addition, some studies point to limitations in VCT service planning and decision making due to the lack of recognition of counselors by local health authorities [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dentre seus achados, verificaram dificuldades de relacionamento com a rede de referência e contrarreferência das pessoas vivendo com HIV pela reduzida oferta de leitos hospitalares e da precariedade dos serviços ambulatoriais. No âmbito internacional, Kabbash et al (2010) realizaram grupos focais com 16 aconselhadores para avaliar serviços de testagem e aconselhamento em HIV do Egito. Os achados dos autores apontaram demandas dos profissionais por melhor capacitação, definição específica de suas atribuições e funções, além de critérios mais claros para avaliar os resultados do seu trabalho, uma vez que ficavam restritos ao número de atendimentos e à percepção subjetiva de cada aconselhador.…”
unclassified